2015
DOI: 10.12688/f1000research.6298.1
|View full text |Cite
|
Sign up to set email alerts
|

Blockade or deletion of transient receptor potential vanilloid 4 (TRPV4) is not protective in a murine model of sepsis

Abstract: Sepsis is a systemic inflammatory response triggered by microbial infection that can cause cardiovascular collapse, insufficient tissue perfusion and multi-organ failure. The cation channel transient receptor potential vanilloid 4 (TRPV4) is expressed in vascular endothelium and causes vasodilatation, but excessive TRPV4 activation leads to profound hypotension and circulatory collapse - key features of sepsis pathogenesis. We hypothesised that loss of TRPV4 signaling would protect against cardiovascular dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…It has been used in multiple studies to describe physiologic changes in response to candidate sepsis therapies; however, this differs from utilizing the technology to define physiologic inclusion criteria to test a therapeutic, as performed here (14, 19, 21, 22, 24, 26, 29, 3335, 38, 39). In our model, coupling of biotelemetry with a CLP model helped quantify physiologic differences in the murine response to sepsis that were indicative of significant biological differences, including inflammation and degree of shock and organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in multiple studies to describe physiologic changes in response to candidate sepsis therapies; however, this differs from utilizing the technology to define physiologic inclusion criteria to test a therapeutic, as performed here (14, 19, 21, 22, 24, 26, 29, 3335, 38, 39). In our model, coupling of biotelemetry with a CLP model helped quantify physiologic differences in the murine response to sepsis that were indicative of significant biological differences, including inflammation and degree of shock and organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a recent study found no protective effect of TRPV4 channel antagonist HC067 on hemodynamic parameters over a 24-hour period in a mouse LPS (12.5 mg/kg, i.v.) endotoxemia model 56 . Furthermore, knockout of the TRPC6 channel was recently reported to protect against LPS-induced lung permeability, inflammation and injury, suggesting a more general role for members of the TRP family in inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In both LPS and CLP models of sepsis inhibition of TRPV4 significantly decreased systemic cytokines, maintained endothelial cell function, and reduced mortality in mice (9). However, there has been contrasting reports on the role of TRPV4 in sepsis, other studies have shown that inhibition has no significant effect on sepsis pathology (106). This inconsistency was found to be due to the antagonist dosage used.…”
Section: Trpv4mentioning
confidence: 94%